Conversion of Wet Glass to Melt at Lower Seismogenic Zone Conditions: Implications for Pseudotachylyte Creep. Issue 20 (21st October 2017) - Proctor, B. P.; Lockner, D. A.; Lowenstern, J. B.; Beeler, N. M.
Abstract: Coseismic frictional melting and the production of quenched glass called pseudotachylyte is a recurring process during earthquakes. To investigate how glassy materials affect the postseismic strength and stability of faults, obsidian gouges were sheared under dry and wet conditions from 200°C to 300°C at 150 MPa effective normal stress. Dry glass exhibited a brittle rheology at all conditions tested, exhibiting friction values and microstructures consistent with siliciclastic materials. Likewise, wet glass at 200°C exhibited a brittle rheology. In contrast, wet gouges at 300°C transitioned from brittle sliding to linear‐viscous (Newtonian) flow at strain rates <3 × 10 −4 s −1, indicating melt‐like behavior. The viscosity ranged from 2 × 10 11 to 7.8 × 10 11 Pa‐s. Microstructures show that viscous gouges were fully welded with rod‐shaped microlites rotated into the flow direction. Fourier transform infrared spectroscopy along with electron backscatter imaging demonstrate that hydration of the glass by diffusion of pore water was the dominant process reducing the viscosity and promoting viscous flow. As much as 5 wt % water diffused into the glass. These results may provide insight into postseismic‐slip behaviors and challenge some interpretations of fault kinematics based on studies assuming that pseudotachylyte formation and flow is solely coseismic. Key Points: Wet rhyolitic glass undergoes Newtonian flow at 300°C and interseismic strain rates Dry rhyolitic glass exhibits brittle deformation at 300°C with frictional properties similar to granite gouge Pseudotachylyte glass under certain conditions might undergo viscous creep in the lower seismogenic zone following earthquakes